Exploring gait velocity as a predictor of cardiometabolic disease risk in young adults - Tanner Thorsen; Nuno Oliveira; Austin Graybeal; Jon Stavres (Frontiers Media S.A., 2024)
BackgroundThe association between poor gait and functional movement ability and metabolic syndrome (MetS) has been well established in older adults. A continuous cardiometabolic risk score, MetSindex, may more easily identify individuals at risk for cardiometabolic disease who do not yet meet the stringent criteria for a formal MetS diagnosis. Although the association between MetS and gait velocity is well established in older adults, no such relationship has been identified in younger adults; a group experiencing a rapid increase in the development of MetS.MethodsMetSindex was determined for 21 young adults using standard procedures. Gait velocity was measured as participants completed a ten-meter walk test. Spatiotemporal parameters of gait were also derived using a motion capture system. Simple linear regression was used to determine the relationship between MetSindex and gait velocity, as well as MetSindex and spatiotemporal parameters of gait.ResultsThere was a large inverse relationship between MetSindex and gait velocity. A large inverse relationship was also observed between MetSindex and cadence, and a large positive relationship was observed between stance time and double limb support time.ConclusionsGait velocity slows in young adults who do not necessarily meet the criterion for positive diagnosis of MetS-but demonstrate an increased risk for MetS and cardiovascular disease through higher MetSindex scores. The mechanism underlying reduced gait velocity may be fewer, but not shorter steps. Determining easy-to-use surrogates of MetS (e.g., gait velocity) may help combat the growing prevalence of MetS by increasing access to preventative approaches.